Effect of Reservoir Sediment Ratio in Soil Media on Arsenic Accumulation in Pineapple (Ananas comosus [L.] Merr.) - Taksinsampan, Supannee; Phewnil, Onanong; Panichsakpatana, Supamard; Tungkananuruk, Kanita (Princess of Naradhiwas University Journal, 2019)
The objective of this research is to solve the contamination of Arsenic in the sediment of the Phu Sawan reservoir in Kaeng Krachan District of Petchaburi Province as it found that there is a lot of sediment in the reservoir and contains arsenic for 26.2 mg/kg, which was exceeded the guideline limit. Therefore, the dredging for agricultural benefit by soil dilution technique is interesting. This article (1) studied the suitable proportion of soil dilution technique towards the growth of pineapple, and (2) examined the accumulation of arsenic in parts of the plant, designed by Completely Randomized Design (CRD) with 4 treatments, 1 normal soil + 3 ratios by weight (Sediment: Soil); 0:1, 1:10, 1:5 and 1:1 and 3 replications. The experimental samples were harvested at 3 growth stages: before flowering stage, flowering stage and harvesting stage. As the result, it was found that the treatment (Sediment : soil = 1:10) provides the best result while the treatment (Sediment : soil = 1:1) gives the low rate of growth. As a result included 3 stages, it was found the arsenic accumulation at the highest rate at the root. The treatment (Sediment : soil = 1:10) has the low arsenic accumulation in roots and leaves which is not different from the normal soil. It was found that the Arsenic accumulation in pineapple fruits of the treatment (Sediment : soil = 1:10) has the lowest value or 0.0134 mg/kg.